A Survey on Blockchain for Information Systems Management and Security. Issue 1 (January 2021) - Berdik, David; Otoum, Safa; Schmidt, Nikolas; Porter, Dylan; Jararweh, Yaser
Highlights: We have investigated the literature and generated a survey regarding the use of blockchain as a tool for application within information systems. An extensive comparison, clustering, and classification have been carried out regarding the current use of blockchain within information systems. We conducted the first blockchain-based information system analysis and addressed all issues in the information systems management area. Abstract: Blockchain technologies have grown in prominence in recent years, with many experts citing the potential applications of the technology in regard to different aspects of any industry, market, agency, or governmental organizations. In the brief history of blockchain, an incredible number of achievements have been made regarding how blockchain can be utilized and the impacts it might have on several industries. The sheer number and complexity of these aspects can make it difficult to address blockchain potentials and complexities, especially when trying to address its purpose and fitness for a specific task. In this survey, we provide a comprehensive review of applying blockchain as a service for applications within today's information systems. The survey gives the reader a deeper perspective on how blockchain helps to secure and manage today information systems. The survey contains a comprehensive reporting on different instances of blockchain studies and applications proposed by the research community and their respective impacts on blockchain and its use across other applications or scenarios. Some of the most important findings this survey highlights include the fact that blockchain's structure and modern cloud- and edge-computing paradigms are crucial in enabling a widespread adaption and development of blockchain technologies for new players in today unprecedented vibrant global market. Ensuring that blockchain is widely available through public and open-source code libraries and tools will help to ensure that the full potential of the technology is reached and that further developments can be made concerning the long-term goals of blockchain enthusiasts.